2020
DOI: 10.1155/2020/9795240
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Brachial-Ankle Pulse Wave Velocity in an Apparently Healthy Chinese Population

Abstract: Purpose. To investigate the factors influencing brachial-ankle pulse wave velocity (baPWV) in an apparently healthy Chinese population, especially the associations between baPWV and indices of blood pressure (BP). Methods. A total of 1123 participants with no history of hypertension were enrolled in this study, and the baPWV and BP of all four limbs were measured along with other covariates. Correlation analyses and multivariate linear regression models were used to identify factors associated with baPWV. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The study concluded a negative correlation between BMI and CAVI, which shares the results of some prior studies 20 21 and echoes the 'obesity paradox' 12 13 that high BMI may benefit people with cardiovascular disease. Such paradoxical relationship between BMI and arteriosclerosis may be explained by the following two aspects: first, bapwv is susceptible to blood pressure, 14 which undermines the accuracy of AS evaluated by bapwv and second, BMI fails to reflect the true picture of obesity, for example, a higher BMI can be found in a strong athlete. However, BFP is a more accurate, reliable and significant indicator to assess overall obesity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study concluded a negative correlation between BMI and CAVI, which shares the results of some prior studies 20 21 and echoes the 'obesity paradox' 12 13 that high BMI may benefit people with cardiovascular disease. Such paradoxical relationship between BMI and arteriosclerosis may be explained by the following two aspects: first, bapwv is susceptible to blood pressure, 14 which undermines the accuracy of AS evaluated by bapwv and second, BMI fails to reflect the true picture of obesity, for example, a higher BMI can be found in a strong athlete. However, BFP is a more accurate, reliable and significant indicator to assess overall obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Such paradoxical relationship between BMI and arteriosclerosis may be explained by the following two aspects: first, bapwv is susceptible to blood pressure, 14 which undermines the accuracy of AS evaluated by bapwv and second, BMI fails to reflect the true picture of obesity, for example, a higher BMI can be found in a strong athlete. However, BFP is a more accurate, reliable and significant indicator to assess overall obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generalized linear analysis was used to study the association between each exercise capacity (VO 2 max, walking speed, handgrip strength, and one-leg standing time) and baPWV, controlling for the identified confounding factors: sex, age, sBP, lean mass, and BMI, and adjusting for smoking, which is a known risk factor for atherosclerosis. [9,[35][36][37] In addition, an active lifestyle was adjusted as a confounding factor. [10] A family history of cardiovascular disease was adjusted for as an additional confounding factor.…”
Section: Statistical Analysesmentioning
confidence: 99%